Sobre la globalización - José Pérez Adán (Universidad de Navarra, 2018)
By contextualising globalization from a sociological perspective it is possible to highlight the experience of inequality as a fruit of fragmentation. The problem lies in the assumption of linear development in the globalization process. This supposition generates deviations, and poverty is one of the most important ones. Finally, an analysis is made of the four dilemmas facing world geopolitics, to conclude with three alternative proposals to the situation described.